Analysis of ASA and Wood Characteristics with Variations in Thickness and Infill Density as 3D Printing Phantom Radiology Material - Suharyana Suharyana; Mohtar Yunianto; Ivara Salsabila Putri Aldicia (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2026)
This research was conducted to identify wood filaments and ASA as potential organ phantoms based on material density, CT number, electron density, effective atomic number, and radiation dose parameters. The thickness and density of the samples were varied to determine the effect on each parameter. The sample image was obtained from a CTScan radiology test with the same exposure factor. The potential of samples as organ phantoms varies for each parameter. In wood filament samples, a thickness of 1 cm to 2 cm with a density of 20% can potentially be a lung organ phantom. Meanwhile, at a thickness of 5 cm with a density of 100%, it can potentially act as a phantom for bone, liver and muscle organs. In ASA filament samples with a thickness of 1 cm to 5 cm with a low density of 20%, it has the potential to be a lung organ phantom and at a density of 100% it has the potential to be an adipose tissue phantom.